A method comparison study of accelerometer based block response times in sprinting - Holmes, J.; Hayes, K.; Harrison, A. J. (ISBS Proceedings Archive (Michigan), 2018)
This study aimed to provide a method comparison of a rail mounted accelerometer for detection of block response-times (RT) with an International Association of Athletic Federation (IAAF) approved automatic start control system (IAAF RT). Twenty national and international sprinters completed sprint trials under simulated race conditions. An accelerometer was placed on the block rail of blocks and RT was determined using visual inspection of the accelerometer signal and using a 3SD threshold method. On average, the visual method detected the RT event 7 ms before, and the 3SD method detected RT 1 ms after the IAAF RT. The results indicated close agreement between the 3SD threshold method and the IAAF RT, however, this highlights the need for further re-examination of threshold-based detection algorithms which may delay the detection of the RT event.